Strategies for Developing Tapis Craft Tourism Villages and Supply Chain in Creative Industries in Negeri Katon Village of Pesawaran, Lampung - Susanti Sundari; Jevri Buari; Suharto Suharto (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
This research discusses the strategy of developing a Tapis craft tourism village and the tourism supply chain in Negeri Katon village, Pesawaran district. The purpose of this study is to identify tourism potential and formulate strategies for developing Tapis craft tourism villages and tourism supply chains. The method used in this study is to use SWOT analysis which includes IFAS, EFAS, IE and SWOT matrices. Based on the results of the research conducted, there are several tourism potentials that can be developed. The IFAS matrix analysis produces 5 strengths and 4 weaknesses, while based on the EFAS matrix analysis there are 3 opportunities and 2 threats. The IE matrix shows that the development of tourist villages is in quadrant one position. The conclusion of this research is that based on the SWOT analysis, there are several alternative strategies that are produced including involving the community in the development of tourist villages starting from planning, implementing and evaluating, making tour package programs, making photo spots for tourists, assisting the community to ensure the program runs well, increasing human resource capabilities, taking advantage of technological developments to maximize promotions, forming tourism management institutions, encouraging people to become entrepreneurs in the culinary field, utilizing and managing people's homes as homestays, building tourist facilities and infrastructure, creating Tapis culture week activity programs, involving the younger generation in exhibition activities, forming the Tapis community, including Tapis lessons in formal schools, improving coordination between craftsmen and the government as well as providing counseling and education to the community.